Pengaruh Knowledge Management Dan Inovasi Berbasis Layanan Terhadap Keberhasilan Bisnis UMKM Kreatif Di Kota Ambon - Merryll Pelamonia (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
The purpose of this study is to investigate the linkages between the implementation of knowledge management and service innovation capability on the business success of the creative UMKM in Ambon City. This type of research is an explanatory study, the analytical approach in research is quantitative research, and the model of this research is survey research. The unit of analysis in this study is the individual creative UMKM entrepreneur in Ambon City. Time horizon of one stage research (cross sectional), data collection using survey methods using questionnaire instruments. Determination of the sample using the probability sampling method, the sample selection in this study used a simple random sampling technique. The sample size analyzed was 53 respondents. Data analysis techniques used inferential statistical analysis (multiple regression). The results of multiple linear regression analysis prove that knowledge management and service-based innovation have a positive effect on the success of creative MSME businesses in Ambon City. Keywords: knowledge management, service-based innovation, business success.